Screening for Hypertension in Asymptomatic Individuals in Nepal: An Expert Consensus Statement - Regmi, Prakash Raj; Sharma, Sanjib Kumar; Bhatt, Yadav Kumar Deo; Malla, Rabi; Maskey, Arun; Limbu, Yubaraj; Nepal, Rajesh; Karn, Achutanand Lal; Dhungana, Sahadeb Prasad; Gautam, Mani Prasad; Kafle, Mukunda Prasad; Maskey, Robin; et al. (Nepalese Heart Journal, 2023)
Hypertension affects a substantial proportion of the general population in Nepal with prevalence ranging from 20 to 30 percent. Early diagnosis and treatment are essential for undiagnosed hypertension and is possible through hypertension screening. The aim of this paper is to provide unified consensus recommendations for the effective screening of hypertension in Nepal. In two National Advisory expert consensus meetings, a total of 42 experts participated, discussed and voted on the key statements for formulating the consensus. Each key statement was scored on a Likert scale ranging from 1 to 9 and a mean score was calculated. The consensus statement was accepted if the mean score was seven or more with the voting of more than two-thirds of the experts. The main consensus recommendations are the following. First, screening for hypertension should start among adults from 18 years of age. Second, effective screening of hypertension can aid in the early diagnosis, control, and improve the cardiovascular disease outcomes. Third, in asymptomatic adults, re-screening is necessary every 3 to 6 months and every 3 to 5 years for initial blood pressure levels of 130-139/80-89 mmHg and